Peran Notaris Dalam Restrukturisasi Perusahaan Non Badan Hukum - Dhifa Nadhira Syadzwina; Esti Setyowati (Jurnal Ilmu Kenotariatan, 2020)
Companies are divided into companies with legal status, namely PT and Cooperative, as well as non – legal companies such as UD, CV, Firm, and Maatschap. Managing a company is not easy so that if there is a decline in business prospects, PT can be restructured by the MKAPP in the Company Law, while the restructuring regulations for Non – Legal Entities are given alternatives through the Partnership in the MSME Law and changes in establishment stipulated by the GMS in the Job Creation Law. This causes the legal vacuum related to whether they can implement the Restructuring of Non – Legal Entities or not, and the Role of Notaries in the obligation to make deeds according to the wishes of the parties. The regulations on the MSME Law and the Job Creation Law have not been able to provide legal certainty regarding the restructuring of Non – Legal Entity Companies even though options have been given in the MSME Law and the Job Creation Law. Therefore, special legislation or implementing regulations are required in Government Regulations related to Restructuring of Non – Legal Entity Companies, and Notaries must always be careful of their authority as public officials.